Water purification by direct solar distillation process in isolated households - doi: 10.4025/actascitechnol.v36i1.18737 - Cardoso da Silva, Márcio Claudio; Sens, Maurício Luiz; Soares, Clarrisa; Andrade Neto, Cícero Onofre de (Acta Scientiarum. Technology, 2014)
This study aims at contributing to the production of drinking water by solar distillation process. Salt raw water and brackish water were used in this process. The objective of this work was to attend rural or isolated households by offering a social and simple utilization technology with low cost materials and good quality water production. The solar drinking water purification has a four-sided pyramidal glass cover allowing the action of sun rays during the day. Water level in the evaporation pan, cover inclination, and water quality were assessed at two points: a) between the parallels 27Â°10´ and 27Â°50´S latitude and meridians 48Â°25´ and 48Â°35´W longitude, from 2003 to 2005, with maximum production of 6.2 L m-2 day, and monthly averages from 3.1 to 3.7 L m-Â² day. b) in the parallels 5Â°47´ and 5Â°57´S latitude and meridians 35Â°12´ and 35Â°22´W longitude, from 2003 to 2004, with monthly averages of 3.0 to 3.7 L m-Â² day. Water quality, physical, chemical and bacteriological parameters comply with recommendations of the World Health Organization - WHO. Â 